Noise Uncertainty Effect on a Modified Two-Stage Spectrum Sensing Technique - Heba A.Tag El-Dien; Rokaia M. Zaki; Mohsen M. Tantawy; Hala M. Abdel-Kader (Institute of Advanced Engineering and Science, 2016)
Detecting the presence or absence of primary user is the key task of cognitive radio networks. However, relying on single detector reduces the probability of detection and increases the probability of missed detection. Combining two conventional spectrum sensing techniques by integrating their individual features improves the probability of detection especially under noise uncertainty. This paper introduces a modified two-stage detection technique that depends on the energy detection as a first stage due to its ease and speed of detection, and the proposed Modified Combinational Maximum-Minimum Eigenvalue based detection as a second stage under noise uncertainty and comperes it with the case of using Maximum-Minimum Eigenvalue and Combinational Maximum-Minimum Eigenvalue as a second stage.